Anode with three-dimensional structure and manufacturing method and application thereof
By designing anode with a three-dimensional structure and using the anode active components of the wave structure, the problem of insufficient deep plating capacity of the existing anode in the BGA position is solved, and higher deep plating capacity and more uniform copper plating effect are achieved, reducing production costs.
Patent Information
- Application Number
- CN202411602800.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-03-07
AI Technical Summary
The existing insoluble anode has insufficient deep plating capacity for small holes in the BGA position, resulting in poor surface copper thickness, low copper plating uniformity and efficiency.
A three-dimensional structure anode is designed. The anode active component has a wave structure. The angle between the wave extension direction and the anode rod is ≤10°. The anode rod and the anode active component are connected through the connecting rod, which optimizes the overall performance of the anode.
The deep plating capacity of VIA holes at the back plate BGA position is improved from 70% to more than 85%, enhancing the uniformity and efficiency of copper plating, and reducing copper consumption and production costs.
Smart Images

Figure CN119571424A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electroplating, and in particular to an anode with a three-dimensional structure and a manufacturing method and application thereof. Background Art
[0002] The rapid development of electronic information technology has promoted the continuous upgrading and updating of electroplating equipment, from the original manual electroplating line and automatic gantry electroplating line to the commonly used VCP line (vertical continuous electroplating line) and horizontal electroplating line. At present, most anode structures are cables connected to the anode rod, titanium baskets are hung on the anode rods, copper balls are placed in the titanium basket bags, and the outer anode bags are produced. Electroplating equipment is a continuous operation equipment. The anode is passivated during the uninterrupted production process, which affects the uniformity and efficiency of electroplating. Therefore, in order to ensure uniformity, the traditional soluble anode pulse line needs to clean the anode regularly for three months and clean the anode mud. The copper consumption for each cleaning is about 10%, resulting in cost waste. The line downtime for maintenance and the time for adjusting the potion are long, resulting in a lower utilization rate and a greater impact on production capacity. In this context, insoluble anodes came into being. Continuous production is achieved through the addition of bath-dissolved copper oxide powder + insoluble anode pulses or bath-dissolved pure copper insoluble anode pulses. The current density can be increased from the working current density of the traditional pulse VCP line of 1.0ASD~1.5ASD to 4.0~5.5ASD, which greatly shortens the electroplating time and improves the production efficiency by 20%~50%. Currently, all the anodes available in the market are planar insoluble anodes. In the electroplating process of printed circuit boards, the throughing power (hereinafter referred to as TP value) is acceptable for boards with a thickness of less than 1.5mm. However, due to the difficulty of electroplating, the impact is more obvious in the electroplating process of boards with an aspect ratio of more than 10:1. For example, the throughing power of the VIA hole (Vertical Interconnect Access Hole) at the BGA (Ball Grid Array) position with a backplane thickness of 5.0mm and a minimum aperture of 0.2mm is the example. The throughing power of the planar insoluble anode is only about 70%, and the TP value is poor. In order to meet the VIA copper thickness requirement, the electroplating must be thickened, and the surface copper thickness at the BGA position will be thicker, which will cause etching difficulties.
[0003] In summary, during the electroplating process, the poor TP value of the existing insoluble anode for the small holes at the BGA position leads to a large difference in surface copper thickness, poor copper plating uniformity, and low copper plating efficiency. Summary of the invention
[0004] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the present invention proposes a three-dimensional anode, which can effectively improve the TP value of the small hole at the BGA position during the electroplating process, and improve the uniformity and efficiency of the electroplating.
[0005] The invention also provides a method for preparing the anode.
[0006] The present invention also provides an electrolysis device comprising the anode.
[0007] The invention also provides application of the electrolysis equipment.
[0008] According to an embodiment of the first aspect of the present invention, there is provided an anode with a three-dimensional structure, the anode comprising:
[0009] Anode rod;
[0010] Anode active component; the anode active component has a wave structure, in which the angle between the extension direction of the wave and the anode rod is ≤10°;
[0011] The wave structure comprises a straight portion and a wave portion which are connected and arranged;
[0012] The shape of the wave portion is at least one of a quadrilateral, a triangle, an arc and an irregular waveform;
[0013] Connecting rod; the connecting rod connects the anode rod and the anode active component.
[0014] The anode according to the embodiment of the present invention has at least the following beneficial effects:
[0015] Compared with the planar anode, the three-dimensional anode provided by the present invention solves the problem of poor deep plating ability of the backplane and other ultra-thick plates, and the deep plating ability of the VIA hole at the BGA position of the electroplated backplane is increased from 70% to more than 85%, thereby improving the deep plating ability of the backplane, reducing the difficulty of etching fine circuits, and improving product quality; at the same time, the improvement of deep plating ability further saves copper consumption and reduces production costs. If the extension direction of the wave in the active part of the anode is changed, for example, when the extension direction of the wave is perpendicular to the anode rod, the deep plating ability will be significantly reduced.
[0016] Furthermore, the present invention further optimizes the comprehensive performance of the obtained three-dimensional anode by limiting the shape of the wave structure.
[0017] According to some embodiments of the present invention, the material of the anode rod includes at least one of stainless steel, titanium and copper, for example, it can be a copper bar wrapped with a titanium layer.
[0018] According to some embodiments of the present invention, the anode rod has a cylindrical or prismatic structure.
[0019] According to some embodiments of the present invention, in the wave structure, the wavelength is 4 to 200 mm. For example, it can be about 4.5 mm, 5 mm, 6 mm, 8 mm, 10 mm, 15 mm, 30 mm, 35 mm, 40 mm, 45 mm, 50 mm, 60 mm, 65 mm, 70 mm, 75 mm, 80 mm, 90 mm, 100 mm, 110 mm, 120 mm, 130 mm, 140 mm, 150 mm, 160 mm, 170 mm, 180 mm or about 190 mm. If there is no special explanation, the wavelength is the length of the minimum repeating unit; if the function of the straight part is only to fix, then the wavelength is defined as the length of the minimum repeating unit of the wave part.
[0020] According to some embodiments of the present invention, in the wave structure, the wave height is 2 to 200 mm, for example, about 2.5 mm, 3 mm, 5 mm, 10 mm, 11 mm, 12 mm, 12.5 mm, 13 mm, 13.5 mm, 14 mm, 20 mm, 50 mm, 100 mm or about 150 mm.
[0021] According to some embodiments of the present invention, the wave structure has a wave degree of 1 to 5000%. The wave degree is the ratio of the wave height to the wavelength.
[0022] According to some embodiments of the present invention, the wave degree of the wave structure is 20-100%, for example, about 30%, 40%, 50%, 60%, 70%, 80% or about 90%.
[0023] According to some embodiments of the present invention, when the shape of the wavy portion includes a quadrilateral, the quadrilateral includes a first side, a second side, and a third side that are connected to each other; the first side and the third side are respectively connected to the second side and the straight portion; and the second side is parallel to the straight portion.
[0024] According to some embodiments of the present invention, the angle between the first side and the second side is 90° to 150°, for example, about 100°, 110°, 120°, 130° or about 140°.
[0025] According to some embodiments of the present invention, the angle between the third side and the second side is 90° to 150°, for example, about 100°, 110°, 120°, 130° or about 140°.
[0026] According to some embodiments of the present invention, the connection between the first side, the second side and the third side is connected by chamfering, wherein the radius of the chamfer used is 0.5 to 50 mm, for example, about 1 mm, 2 mm, 5 mm, 10 mm, 15 mm, 20 mm, 25 mm, 30 mm, 35 mm, 40 mm or about 45 mm.
[0027] According to some embodiments of the present invention, when the shape of the wave portion includes a triangle, the triangle includes a side A and a side B that are connected.
[0028] According to some embodiments of the present invention, the angle between the side A and the side B is 5° to 150°, for example, about 10°, 30°, 50°, 60°, 70°, 90°, 100°, 120° or about 140°.
[0029] According to some embodiments of the present invention, the side A and the side B are connected by chamfering, wherein the radius of the chamfering is 0.5 to 50 mm, for example, about 1 mm, 2 mm, 5 mm, 10 mm, 15 mm, 20 mm, 25 mm, 30 mm, 35 mm, 40 mm or about 45 mm.
[0030] According to some embodiments of the present invention, when the shape of the wave portion includes an irregular waveform, the irregular waveform is a deformation of the quadrilateral, specifically a deformation of the second side; further specifically, part or all of the second side is replaced with an arc, a square or a V-shape. According to some embodiments of the present invention, in the wave structure, the straight portion and the wave portion are connected by chamfering. Specifically, the radius of the chamfer used is 0.5 to 50 mm. For example, it can be about 1 mm, 2 mm, 5 mm, 10 mm, 15 mm, 20 mm, 25 mm, 30 mm, 35 mm, 40 mm or about 45 mm.
[0031] According to some embodiments of the present invention, the wave structure includes straight portions and wave portions that are arranged at intervals and in a cycle.
[0032] According to some embodiments of the present invention, the wave structure consists of a straight portion, a wave portion and a straight portion that are connected to each other.
[0033] According to some embodiments of the present invention, the wave structure consists of a wave portion, a straight portion, a wave portion, a straight portion and a wave portion that are connected to each other.
[0034] The wave portion is composed of one or more waveforms (such as a single quadrilateral, an arc, a triangle, and an irregular shape).
[0035] According to some embodiments of the present invention, the angle between the extension direction of the waves in the wave structure and the anode rod is ≤5°. More specifically, the extension direction is parallel to the anode rod.
[0036] According to some embodiments of the present invention, the wave structure is a wave structure with two-way protrusions. There is no difference between the front and the back during use.
[0037] According to some embodiments of the present invention, the wave structure is a unidirectional raised wave structure. During use, the raised wave shape faces the cathode. Compared with the bidirectional raised wave structure, the unidirectional raised wave structure has more waves facing the cathode and a better copper plating effect; and if it is a bidirectional raised wave structure, the raised part facing away from the cathode will offset the part raised toward the cathode.
[0038] According to some embodiments of the present invention, the anode active component is a plate-like structure.
[0039] According to some embodiments of the present invention, the anode active component is provided with a hollow grid (which can also be described as a mesh structure), thereby increasing the specific surface area of the anode active component and significantly improving the contact area between the anode active component and the tank liquid during use.
[0040] According to some embodiments of the present invention, the hollow grid is a parallelogram.
[0041] According to some embodiments of the present invention, the size of the parallelogram is (2.5-3.5) mm×(5.5-6.5) mm, for example, about 3 mm×6 mm.
[0042] According to some embodiments of the present invention, a fixing hole is provided on the anode active component.
[0043] According to some embodiments of the present invention, the anode active component includes a titanium-based substrate and an iridium-tantalum coating disposed on the surface of the titanium-based substrate, thereby improving the insolubility of the anode, improving the production capacity of the electrolysis equipment including the anode, avoiding the waste of copper, and saving costs.
[0044] According to some embodiments of the present invention, the titanium-based substrate is made of at least one of titanium or titanium alloy.
[0045] According to some embodiments of the present invention, the thickness of the titanium-based substrate is 1 to 2 mm.
[0046] According to some embodiments of the present invention, the thickness of the iridium-tantalum coating is 0.1-3 μm, for example, about 0.5 μm or about 1 μm.
[0047] According to some embodiments of the present invention, the iridium-tantalum coating comprises iridium dioxide and tantalum pentoxide.
[0048] According to some embodiments of the present invention, the anode active component further includes an intermediate layer disposed between the titanium-based substrate and the iridium-tantalum coating.
[0049] According to some embodiments of the present invention, the intermediate layer includes at least one of a titanium layer, a titanium-tantalum layer and a titanium-zirconium layer. Thus, on the one hand, the adhesion between the titanium-based substrate and the iridium-tantalum coating is increased, and on the other hand, if the iridium-tantalum coating fails and needs to be polished and re-coated, the intermediate layer also has the function of protecting the titanium-based substrate, significantly extending the service life of the anode active component and reducing the cost of the anode active component.
[0050] According to some embodiments of the present invention, the thickness of the intermediate layer is 0.1-2 μm, for example, about 0.15 μm, 0.3 μm, 0.5 μm or about 1 μm.
[0051] According to some embodiments of the present invention, the connecting rod is a titanium rod.
[0052] According to some embodiments of the present invention, the connecting rod comprises a transverse rod arranged parallel to the extension direction of the wave; and a longitudinal rod arranged perpendicular to the extension direction of the wave. Thus, the transverse rod prevents the anode active component from being deformed, and the longitudinal rod connects the anode rod to fix it.
[0053] According to some embodiments of the present invention, the transverse rod and the longitudinal rod are connected to the anode active component through the fixing hole.
[0054] According to some embodiments of the present invention, the number of the transverse rods is ≥2.
[0055] According to some embodiments of the present invention, the number of the longitudinal rods is ≥2.
[0056] According to some embodiments of the present invention, the single transverse rod and the single longitudinal rod have intersecting fixing points.
[0057] On the whole, the anode provided by the present invention has both deep plating ability and durability due to its structural and material design, and is particularly suitable for continuous production of attached tank-dissolved copper oxide powder + insoluble anode pulse or attached tank-dissolved pure copper insoluble anode pulse; it can not only improve production efficiency, but also improve deep plating ability, further save copper consumption, and reduce production costs.
[0058] According to an embodiment of the second aspect of the present invention, a method for preparing the anode is provided, the method comprising the following steps:
[0059] S1. Bending the semi-finished product of the anode active component and setting the wave structure;
[0060] S2. Connecting the anode active component and the anode rod with the connecting rod.
[0061] Since the preparation method adopts all the technical solutions of the anode of the above embodiment, it has at least all the beneficial effects brought by the technical solutions of the above embodiment.
[0062] In addition, the preparation method is simple to operate, easy to implement, and convenient for large-scale promotion in industry.
[0063] According to some embodiments of the present invention, in step S1, the provision of the semi-finished product includes providing a hollow grid and fixing holes on a titanium-based substrate with a planar structure.
[0064] According to some embodiments of the present invention, step S1 further comprises dry sandblasting and cleaning the obtained component after the bending, wherein the dry sandblasting adopts cast iron G120 specification.
[0065] According to some embodiments of the present invention, the cleaning includes heated acidic water washing. The temperature is 85±5°C. The acidic water used for the acidic water washing is an aqueous sulfuric acid solution, and the mass concentration of the aqueous sulfuric acid solution is 5-15%; for example, it can be about 5% or about 10%. The cleaning speed is 2.5m / min±0.2m / min. The cleaning also includes drying after the heated acidic water washing. The drying temperature is 85°C±5°C.
[0066] According to some embodiments of the present invention, the preparation method further comprises providing an iridium-tantalum coating between step S1 and step S2.
[0067] According to some embodiments of the present invention, the method for providing the iridium-tantalum coating includes coating a dispersion containing an iridium-tantalum mixture on the surface of the semi-finished product obtained in step S1, and sintering.
[0068] According to some embodiments of the present invention, the dispersoid of the dispersion includes a soluble iridium salt and a soluble tantalum salt. The molar ratio of iridium atoms to tantalum atoms is 6.5 to 7.5:3. For example, it can be about 7:3. The sum of the concentrations of the iridium salt and the tantalum salt in the dispersion is 0.001 to 0.01 mol / L. For example, it can be about 0.003 mol / L, or about 0.005 mol / L.
[0069] According to some embodiments of the present invention, the dispersant of the dispersion includes at least one of isopropanol and n-butanol. Further, the dispersant includes isopropanol and n-butanol. The mass ratio of isopropanol to n-butanol is 1.5 to 2.5:1. For example, it can be about 2:1.
[0070] According to some embodiments of the present invention, the coating and sintering are repeated ≥ 5 times. In actual production, the number of repetitions is based on the required thickness of the iridium-tantalum coating, for example, 10 times, 15 times or 20 times.
[0071] According to some embodiments of the present invention, the sintering temperature of the iridium-tantalum coating is 450-650° C. For example, it may be about 550° C.
[0072] According to some embodiments of the present invention, the sintering time of the iridium-tantalum coating is 10 to 30 minutes, for example, about 15 minutes, 20 minutes, or 25 minutes.
[0073] According to some embodiments of the present invention, the preparation method further comprises providing the intermediate layer after step S1 and before providing the iridium-tantalum coating.
[0074] According to some embodiments of the present invention, the method of providing the intermediate layer includes magnetron sputtering.
[0075] According to some embodiments of the present invention, when the intermediate layer is a titanium-tantalum layer, the target material used for the magnetron sputtering is a titanium-tantalum target material, wherein the mass ratio of titanium to tantalum is 2.0 to 3:1, for example, about 2.3:1, 63:27 or about 2.5:1.
[0076] According to some embodiments of the present invention, the vacuum degree of the magnetron sputtering is 1.0-1.5×10 -2 Pa. For example, it can be about 1.25×10 -2 Pa.
[0077] According to some embodiments of the present invention, the temperature of the magnetron sputtering is 450-500°C.
[0078] According to some embodiments of the present invention, the magnetron sputtering is performed in a protective atmosphere. The protective atmosphere includes at least one of argon and nitrogen; for example, a mixture of nitrogen and argon in a volume ratio of 3:42 to 48. More specifically, the volume ratio of nitrogen to argon is about 3:45.
[0079] According to some embodiments of the present invention, the flow rate of the protective atmosphere is 25-35 SCCM.
[0080] According to some embodiments of the present invention, the power of the magnetron sputtering is 280-480W.
[0081] According to some embodiments of the present invention, the magnetron sputtering duration is 15-20 minutes, and the thickness of the alloy on sputtering is controlled to be 0.1-2 μm, for example, specifically about 0.15 μm.
[0082] According to an embodiment of the third aspect of the present invention, there is provided an electrolysis device, the electrolysis device comprising:
[0083] Electrolyzer;
[0084] An electrolyte, wherein the electrolyte is disposed inside the electrolytic cell;
[0085] The anode provided by the embodiment of the first aspect of the present invention; the anode rod is fixed to the wall of the electrolytic cell, and the anode active component is at least partially immersed in the electrolyte;
[0086] A cathode is at least partially immersed in the electrolyte and is arranged opposite to the anode.
[0087] Since the electrolytic device adopts all the technical solutions of the anode of the above embodiment, it has at least all the beneficial effects brought by the technical solutions of the above embodiment, that is, the PCB board electroplated by the electrolytic device has good deep plating ability.
[0088] According to some embodiments of the present invention, the area ratio of the anode to the cathode is 1.5 to 2: 1. The area ratio is the area ratio of a single anode to a single cathode.
[0089] According to an embodiment of the fourth aspect of the present invention, a method for electroplating a PCB board using the electrolytic equipment is provided.
[0090] Since the method adopts all the technical solutions of the electroplating equipment of the above-mentioned embodiment, it has at least all the beneficial effects brought by the technical solutions of the above-mentioned embodiment.
[0091] According to some embodiments of the present invention, in the electroplating, the electrolyte satisfies at least one of the following parameters:
[0092] (1) Copper sulfate 230-250g / L;
[0093] (2) Sulfuric acid 40-60 g / L;
[0094] (3) Chloride ion 50-90 ppm;
[0095] (4) Temperature: 20-25℃.
[0096] According to some embodiments of the present invention, the electrolyte further includes a copper plating additive. The type and amount of the copper plating additive are adjusted as needed and are not strictly limited herein.
[0097] According to some embodiments of the present invention, during the electroplating, the current density is 100-400A / m 2 .
[0098] If there is no special explanation, the actual meaning of “about” in the present invention is that the error is allowed to be within the range of ±2%, for example, about 100 is actually 100±2%×100.
[0099] Unless otherwise specified, “between” in the present invention includes the number itself, for example, “between 2 and 3” includes the endpoint values 2 and 3.
[0100] Other features and advantages of the present invention will be set forth in the description which follows, and in part will be apparent from the description, or may be learned by practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0101] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0102] Figure 1 It is a schematic diagram of the structure of the anode provided in Example 1 of the present invention.
[0103] Figure 2 The present invention Figure 1 Schematic diagram of the front view of the anode active components.
[0104] Figure 3 The present invention Figure 1 Schematic top view of the anode active component.
[0105] Figure 4 It is a structural schematic diagram of the electrolysis equipment in the application example of the present invention.
[0106] Figure 5 Schematic diagram of the structure of the cathode used in the application example of the present invention.
[0107] Figure 6 It is a schematic diagram of calculation parameters of the deep plating capability TP in the test example of the present invention.
[0108] Figure 7 Schematic top view of the anode active component in Example 3 of the present invention.
[0109] Figure 8 It is a schematic top view of the anode active component in Example 4 of the present invention.
[0110] Fig. 9 It is a schematic top view of the anode active component in Examples 5 to 7 of the present invention.
[0111] Fig.10 It is a schematic top view of the anode active component in Examples 8 to 10 of the present invention.
[0112] Fig.11 It is a schematic top view of the anode active component in Examples 11 to 13 of the present invention.
[0113] Reference numerals:
[0114] Anode 100 , anode rod 110 , anode active component 120 , fixing hole 121 , straight portion 121 , wave portion 122 , first side 1221 , second side 1222 , third side 1223 ; side A 1224 , side B 1225 ; connecting rod 130 .
[0115] cathode 200; BGA area 210;
[0116] Electrolytic cell 300. DETAILED DESCRIPTION
[0117] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present invention, and cannot be understood as limiting the present invention.
[0118] In the description of the present invention, it should be understood that descriptions involving orientations, such as up, down, front, back, left, right, etc., and orientations or positional relationships indicated are based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the present invention.
[0119] In the description of the present invention, unless otherwise clearly defined, terms such as setting, installing, connecting, etc. should be understood in a broad sense, and technicians in the relevant technical field can reasonably determine the specific meanings of the above terms in the present invention based on the specific content of the technical solution.
[0120] Example 1
[0121] refer to Figures 1 to 3 , this example provides an anode with a three-dimensional structure, which is composed of the following components:
[0122] Anode rod 110; specifically, a cylindrical stainless steel rod;
[0123] Anode active component 120; The anode active component 120 has a wave structure, in which the extension direction of the wave (the direction indicated by the arrow or the opposite direction thereof) is parallel to the anode rod 110; The structure is as follows Figure 3 As shown, during use, Figure 3 , the side marked H (upward side) faces the cathode.
[0124] The wave structure is composed of a wave portion 122, a straight portion 121, a wave portion 122, a straight portion 121 and a wave portion 122 which are connected in sequence; the straight portion 121 is only used for fixing.
[0125] One wave portion is composed of a plurality of connected waveforms, each waveform is arc-shaped, and the chord length L (ie wavelength) of each arc is about 33 mm.
[0126] Connecting rod 130; The connecting rod 130 connects the anode rod 110 and the anode active component 120 and is made of titanium.
[0127] The anode active component 120 includes a titanium substrate (made of pure titanium, 2 mm thick) and an intermediate layer and an iridium-tantalum coating that sequentially cover the surface of the titanium substrate; the intermediate layer is a titanium-tantalum layer (atomic ratio, titanium: tantalum = 73:27), with a thickness of 0.1 to 0.15 μm (the thickness at different positions is almost the same, but it can fluctuate within this range); the thickness of the iridium-tantalum layer is 0.1 to 0.3 μm (the thickness at different positions is almost the same, but it can fluctuate within this range, and the thickness in this example is about 1 μm), and the effective components are iridium dioxide and tantalum pentoxide, and the atomic ratio of iridium to tantalum is about 7:3. The length of the anode active component 120 is 330 mm (the extension length of the wave) and the width is 750 mm.
[0128] It can be understood that in the anode active component 120, the wave height H of the wave structure is about 11 mm, and the wave portion H / L is about 33%.
[0129] It is understandable that the anode active component 120 is provided with a hollow grid (not shown in the figure) with a size of 3 mm×6 mm and a parallelogram shape.
[0130] It is understandable that a fixing hole 121 is provided on the anode active component 120 .
[0131] It is understandable that the connecting rod 130 includes two transverse rods (set at a position parallel to the extension direction of the wave structure) and two longitudinal rods. The transverse rod is bent to fit the wave structure and is fixed to the anode active component 120 through the fixing hole 121 by means of screws; the longitudinal rod is set at a position perpendicular to the extension direction of the wave structure, one end of the longitudinal rod passes through the fixing hole 121 and is fixed to the intersection of the transverse rod and the anode active component 120 by means of screws, and the other end is welded to the anode rod 110.
[0132] Example 2
[0133] In this example, the anode provided in Example 1 was prepared, and the specific steps were as follows:
[0134] D1. A hollow grid and fixed holes are arranged on the titanium substrate, and the titanium substrate is bent to form the required wave degree of Example 1. The bending device is a fully automatic bending machine.
[0135] D2. Dry sandblasting, cleaning, and magnetron sputtering to form an intermediate layer on the surface of the component obtained in step D1.
[0136] The sand used for dry sandblasting is cast iron G120 specification.
[0137] During the cleaning process, the cleaning line is run at a speed of 2.5m / min±0.2m / min. During the cleaning process, the temperature is about 85°C, the concentration of the pickling sulfuric acid solution is about 10%, and the drying temperature is 85°C±5°C.
[0138] During the magnetron sputtering process, titanium-tantalum targets were used, and the magnetron sputtering process parameters were: -2 Under the vacuum degree of Pa, the cleaned parts were preheated to 180°C, the flow rate of the protective atmosphere was controlled to 35 SCCM, and the target sputtering power was controlled to 280 W. In the protective atmosphere, N2:Ar=3:45, the sputtering power was 280 W, and the sputtering time was 20 min. In the titanium-tantalum target material used, the mass ratio of titanium to tantalum was about 63:27.
[0139] D3. Set up iridium-tantalum coating: mix chloroiridic acid and tantalum pentachloride in the ratio of iridium: tantalum = 7:3 (molar ratio), dissolve in a mixed solvent formed by isopropanol: n-butanol = 2:1 volume ratio, and the total concentration of iridium salt and tantalum salt in the obtained solution is 0.005 mol / L. After stirring evenly, apply it on the surface of the component obtained in step D2 and then sinter; the coating method includes spraying. The sintering temperature is about 550°C, and the duration is 10 to 30 minutes (about 20 minutes in this example). In this example, the spraying-sintering steps are repeated 15 times to ensure that the thickness of the iridium-tantalum coating is about 1μm.
[0140] The component obtained in this step is the anode active component 120 .
[0141] D4. Connection:
[0142] The two transverse rods are punched and bent to transversely fix the anode active component 120 . One end of the two longitudinal rods is fixed at the intersection of the transverse rods and the anode active component 120 , and the other end is welded to the anode rod 110 .
[0143] Example 3
[0144] refer to Figure 7 This example provides and prepares an anode with a three-dimensional structure, and the specific structure is different from that of Example 1 in that:
[0145] The wave structure is composed of a straight portion 121 and a wave portion 122 which are sequentially connected and spaced apart from each other, wherein each wave portion 122 is composed of a waveform, and each waveform is a quadrilateral, specifically a chamfered trapezoid.
[0146] Furthermore, the straight portion 121 and the wavy portion 122 are connected by a chamfer with a radius of 1 mm;
[0147] Each chamfered trapezoid is a first side 1221, a second side 1222 and a third side 1223 connected by a chamfer with a radius of 1 mm; the second side is parallel to the straight portion. The angle between the first side 1221 and the second side 1222 is 100°; the angle between the second side 1222 and the third side 1223 is 100°;
[0148] An adjacent wave portion 122 and a straight portion 121 form a complete wave with a wavelength of 100 mm and a wave height of 80 mm.
[0149] In this example, the preparation process of the anode is the same as that of Example 2.
[0150] Example 4
[0151] refer to Figure 8 This example provides and prepares an anode with a three-dimensional structure, and the specific structure is different from that of Example 1 in that:
[0152] The wave structure consists of a straight portion 121 (only for fixing), a wave portion 122 and a straight portion 121 (only for fixing), wherein each wave portion 122 consists of a plurality of waveforms (only 3 waveforms are shown in the figure for ease of display), and each waveform is a triangle.
[0153] Furthermore, the straight portion 121 and the wavy portion 122 are directly connected;
[0154] Each triangle is composed of a side A 1224 and a side B 1225 connected by a chamfer with a radius of 1 mm; the angle between the side A 1224 and the side B 1225 is 60°.
[0155] The wave structure has a wavelength of 100 mm and a wave height of 80 mm.
[0156] In this example, the preparation process of the anode is the same as that of Example 2.
[0157] Example 5
[0158] refer to Fig. 9 This example provides and prepares an anode with a three-dimensional structure, and the specific structure is different from that of Example 1 in that:
[0159] The wave structure is composed of a straight portion 121 and a wave portion 122 arranged in sequence. The wave portion 122 is a triangle and a quadrilateral (arranged in turn) arranged in sequence. The parameters of the triangle are similar to those of the triangle in Example 4, except that the adjacent sides are directly connected instead of being connected by chamfers; the parameters of the quadrilateral are similar to those of the quadrilateral in Example 3, except that the adjacent sides are directly connected instead of being connected by chamfers.
[0160] The wave structure has a wavelength of 100 mm and a wave height of 80 mm.
[0161] In this example, the preparation process of the anode is the same as that of Example 2.
[0162] Example 6
[0163] refer to Fig. 9 This example provides and prepares an anode with a three-dimensional structure, and the specific structure is different from that of Example 1 in that:
[0164] The wave structure is composed of a straight portion 121 and a wave portion 122 arranged in sequence. The wave portion 122 is an arc and a quadrilateral (arranged in turn) arranged in sequence. The arc is a semicircle with a diameter of 25 mm, and the arc and the straight portion are directly connected without being connected by chamfering; the parameters of the quadrilateral are similar to those of the quadrilateral in Example 3, except that the adjacent sides are directly connected without being connected by chamfering.
[0165] The wave structure has a wavelength of 100 mm and a wave height of 80 mm.
[0166] In this example, the preparation process of the anode is the same as that of Example 2.
[0167] Example 7
[0168] refer to Fig. 9 This example provides and prepares an anode with a three-dimensional structure, and the specific structure is different from that of Example 1 in that:
[0169] The wave structure is composed of a straight portion 121 and a wave portion 122 arranged in sequence. The wave portion 122 is an arc and a triangle (arranged in turn) arranged in sequence. The arc is a semicircle with a diameter of 25 mm, and the arc and the straight portion are directly connected without being connected by chamfering; the parameters of the triangle are similar to those of the triangle in Example 4, except that the adjacent sides are directly connected without being connected by chamfering.
[0170] The wave structure has a wavelength of 100 mm and a wave height of 80 mm.
[0171] In this example, the preparation process of the anode is the same as that of Example 2.
[0172] Example 8
[0173] refer to Fig.10 This example provides and prepares an anode with a three-dimensional structure, and the specific structure is different from that of Example 3 in that:
[0174] (1) A semicircle is provided on the second side 1222 facing the straight portion 121, and the diameter of the semicircle is 25 mm.
[0175] (2) In the wave structure, the components are directly connected to each other and are not connected by chamfers.
[0176] Example 9
[0177] refer to Fig.10 This example provides and prepares an anode with a three-dimensional structure, and the specific structure is different from that of Example 3 in that:
[0178] (1) A square is provided on the second side 1222 and faces the straight portion 121 , and the side length of the square is 25 mm.
[0179] (2) In the wave structure, the components are directly connected to each other and are not connected by chamfers.
[0180] Example 10
[0181] refer to Fig.10 This example provides and prepares an anode with a three-dimensional structure, and the specific structure is different from that of Example 3 in that:
[0182] (1) A triangle is provided on the second side 1222 and faces the straight portion 121 . The triangle is an equilateral triangle with a side length of 25 mm.
[0183] (2) In the wave structure, the components are directly connected to each other and are not connected by chamfers.
[0184] Embodiment 11
[0185] refer to Fig.11 This example provides and prepares an anode with a three-dimensional structure, and the specific structure is different from that of Example 8 in that:
[0186] (1) Replace the semicircle on the second side with an arc. The chord length of the arc is the length of the second side, and the central angle of the arc is 30°.
[0187] (2) In the wave structure, the components are directly connected to each other and are not connected by chamfers.
[0188] Embodiment 11
[0189] refer to Fig.11 This example provides and prepares an anode with a three-dimensional structure, and the specific structure is different from that of Example 4 in that:
[0190] (1) Each waveform is a variant quadrilateral. The specific variant quadrilateral is different from that in Example 8 in that the semicircle on the second side 1222 is replaced by an arc, the chord length of the arc is equal to the side length of the second side 1222, and the central angle of the arc is 150°.
[0191] (2) In the wave structure, the components are directly connected to each other and are not connected by chamfers.
[0192] Example 12
[0193] refer to Fig.11 This example provides and prepares an anode with a three-dimensional structure, and the specific structure is different from that of Example 4 in that:
[0194] (1) Each waveform is a variant quadrilateral. The specific variant quadrilateral is different from that in Embodiment 10 in that the side length of the triangle on the second side 1222 is equal to the side length of the second side 1222 .
[0195] (2) In the wave structure, the components are directly connected to each other and are not connected by chamfers.
[0196] Example 13
[0197] refer to Fig.11 This example provides and prepares an anode with a three-dimensional structure, and the specific structure is different from that of Example 4 in that:
[0198] (1) Each waveform is a quadrilateral, and the specific quadrilateral is the same as that in Embodiment 3.
[0199] (2) In the wave structure, the components are directly connected to each other and are not connected by chamfers.
[0200] Examples 14 to 26 respectively prepare an anode with a three-dimensional structure, specifically:
[0201] The structural difference from Example 1 lies in the difference in wave height H and wave degree, and the specific differences are shown in Table 1.
[0202] The preparation method is similar to that of Example 2, and only the bending parameters need to be adjusted in the bending of step D1 to obtain the corresponding wave structure.
[0203] Comparative Example 1
[0204] This example prepares an anode with a three-dimensional structure, and the specific structure is different from that of Example 1 in that:
[0205] In the anode active component, the extension direction of the wave (the direction indicated by the arrow or the opposite direction) is perpendicular to the anode rod 110 .
[0206] Comparative Example 2
[0207] This example prepares an anode, and the specific structure is different from that of Example 1 in that:
[0208] No bending is performed in step D1.
[0209] Application Example 1
[0210] refer to Figure 4 , this example provides an electrolysis device, the specific structure is:
[0211] Electrolytic cell 300;
[0212] Electrolyte, the electrolyte is disposed inside the electrolytic cell 300;
[0213] Anode 100; in anode 100, anode rod 110 is fixed on the wall of electrolytic cell 300, and anode active component 120 is at least partially immersed in electrolyte; the anode of this example comes from the above embodiment or comparative example.
[0214] The cathode 200 is at least partially immersed in the electrolyte and is arranged opposite to the anode 100. The specific structure of the cathode 200 used in this example is as follows: Figure 5 As shown, the cathode 200 is 700 mm long, 500 mm wide and 5 mm thick. The cathode 200 includes a BGA region 210 and other regions; the BGA region 210 is distributed at the four corners and the center of the cathode 200; the length and width of each BGA region 210 are 96 mm respectively, and the distance between the BGA region 210 located at the four corners and the cathode 200 is about 22 mm; it can be further understood that dense holes (also called small hole arrays) are distributed within the BGA region 210, and holes are also distributed in other regions, but the density of the holes is lower than the distribution density of the dense holes.
[0215] It can be appreciated that the area ratio of the anode and cathode active areas is 1.8:1.
[0216] It can be further understood that there are two anodes 100 , which are respectively disposed on both sides of the cathode 200 .
[0217] Application Example 2
[0218] This example uses the electrolytic equipment obtained in Application Example 1 for electroplating, specifically:
[0219] In electroplating, the electrolyte meets the following parameters:
[0220] (1) Copper sulfate 240 g / L;
[0221] (2) Sulfuric acid 50 g / L;
[0222] (3) Chloride ion 70 ppm;
[0223] (4) Temperature: 20-25℃.
[0224] During the electrolysis process, the copper ions in the electrolyte will be consumed, so copper oxide powder needs to be added to maintain the copper ion content. The above parameters are all parameters during slotting. As the electrolysis progresses, there will be a certain degree of change, but it will not affect the performance.
[0225] Control current density is 150A / m2 .
[0226] The thickness of the test board (ie, the cathode 200 used in Application Example 1) is 5.0 mm, the minimum aperture is 0.25 mm, and the aspect ratio is 5 / 0.25 = 20: 1. 50 test boards are electroplated in each group, and the average value is finally taken.
[0227] Test Case
[0228] This example counts the deep plating capability (TP value) of the BGA position holes in the test board after electroplating in Application Example 2, and calculates the average TP value. The calculation formula for the TP value is:
[0229]
[0230] Among them, 1-6 are the hole copper thickness plated by the electroplating process at the indicated position, ad is the surface copper thickness plated by the electroplating process at the indicated position (the unit must be kept the same as the hole copper thickness), and each numbered position is as follows Figure 6 shown.
[0231] This example also calculates the extreme difference in copper thickness on the test board surface, that is, the difference between the thickest thickness and the thinnest thickness, and takes multiple test boards to calculate the average value.
[0232] The results are shown in Table 1.
[0233] Table 1 Anode parameters and BGA position hole TP value results in the embodiments and comparative examples
[0234] Group H mm Waviness TP value (Avg) Copper thickness range μm Example 1 11.0 33% 87.34% 9.3 Embodiment 14 10.0 20% 86.29% 9.2 Embodiment 15 12.5 30% 86.93% 9.1 Example 16 12.5 20% 85.36% 9.5 Embodiment 17 15.0 10% 85.19% 9.8 Embodiment 18 10.0 20% 86.33% 9.6 Embodiment 19 15.0 20% 86.67% 9.5 Embodiment 20 10.0 10% 82.41% 9.7 Embodiment 21 12.5 10% 85.59% 9.6 Embodiment 22 15.0 30% 89.30% 9.0 Embodiment 23 13.34 33.7% 87.26% 9.3 Embodiment 24 3 30% 75.22% 18.4 Embodiment 25 2 30% 73.45% 19.7 Embodiment 26 1 30% 71.18% 20.5 Comparative Example 1 12.5 30% 77.15% 21.3 Comparative Example 2 0 0 70.15 20.86
[0235] The results in Table 1 show that the greater the wave height H of the anode wave structure, the better the deep plating ability of the test board when the same electroplating conditions are used; the greater the wave degree of the wave-shaped anode, the better the deep plating ability; there is no interaction between thickness and wave degree; but if the wave height and wave degree continue to increase, the distance between the cathode and the anode may be reduced, thereby affecting the electroplating process. In actual production, anodes with different H and different wave degrees can be made according to the requirements of the electrolytic cell to improve the deep plating ability of the dense holes at the BGA position of the backplane.
[0236] On the whole, the present invention increases the deep plating ability of the VIA hole at the BGA position of the electroplated backplane from 70% to 85% (or even higher) compared with the planar anode active component by setting the structure of the anode active component, thereby improving the deep plating ability of the BGA position hole of the backplane, reducing the difficulty of etching fine circuits, and improving product quality; at the same time, the improvement of the through-hole property further saves copper consumption and reduces production costs.
[0237] Furthermore, the present invention also analyzes the reason why the structure of the anode active component affects the deep plating ability: the voltage drop on the two parallel circuits of the near cathode (cathode corresponding to the anode peak) and the anode, and the far cathode (cathode corresponding to the anode trough) and the anode should be equal, that is:
[0238]
[0239] From this we get:
[0240]
[0241] in l2=l1+Δl, and we can get:
[0242]
[0243] Where I1, I2 - the current intensity near the cathode and far cathode;
[0244] R1, R2 - resistance of electrolyte between near cathode and far cathode and anode;
[0245] - electrode potentials near the cathode and far from the cathode;
[0246] Δl – the difference between the distances between the far cathode and the near cathode and the anode;
[0247] ——cathodic polarizability;
[0248] The difference (Δl) between the distance between the far and near cathode and the anode can be seen from Formula 3. When Δl approaches zero, it helps to distribute the current on the cathode surface. This means that when the anode is a flat plate, the thinner the plate is and the closer it is to the plane, the more uniform the current distribution will be. On the contrary, the thicker the plate is, the more objectively uneven the current distribution will be. In order to make the current distribution on the ultra-thick plate complex and uneven, thereby increasing the TP value of the dense holes in the BGA part, the present invention designs a three-dimensional anode, taking the wave shape as an example.
[0249] Furthermore, compared with other embodiments, the anodes provided in embodiments 3 to 13 have a larger surface area in the same projected area. It can be expected that when the anodes of embodiments 3 to 13 are used for electroplating, they have a better electroplating effect.
[0250] The embodiments of the present invention are described in detail above in conjunction with the accompanying drawings, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.
Claims
1. A three-dimensional anode, characterized in that: The anode comprises: Anode rod; Anode active component; the anode active component has a wave structure, in which the angle between the extension direction of the wave and the anode rod is ≤10°; The wave structure comprises a straight portion and a wave portion which are connected and arranged; The shape of the wave portion is at least one of a quadrilateral, a triangle, an arc and an irregular waveform; Connecting rod; the connecting rod connects the anode rod and the anode active component.
2. The anode according to claim 1, characterized in that In the wave structure, the wavelength is 4 to 200 mm; and / or, in the wave structure, the wave height is 2 to 200 mm.
3. The anode according to claim 1 or 2, characterized in that: When the shape of the wave portion includes a quadrilateral, the quadrilateral includes a first side, a second side and a third side that are connected; the first side and the third side are respectively connected to the second side and the straight portion; and the second side is parallel to the straight portion.
4. The anode according to claim 3, characterized in that The angle between the first side and the second side is 90° to 150°; and / or the angle between the third side and the second side is 90° to 150°.
5. The anode according to claim 1 or 2, characterized in that: When the shape of the wave portion includes a triangle, the triangle includes a side A and a side B that are connected.
6. The anode according to claim 5, characterized in that The angle between the side A and the side B is 5° to 150°.
7. The anode according to claim 1, characterized in that The anode active component comprises a titanium-based substrate and an iridium-tantalum coating arranged on the surface of the titanium-based substrate.
8. A method for preparing an anode according to any one of claims 1 to 7, characterized in that: The preparation method comprises the following steps: S1. Bending the semi-finished product of the anode active component and setting the wave structure; S2. Connecting the anode active component and the anode rod with the connecting rod.
9. An electrolysis device, characterized in that: The electrolysis equipment comprises: Electrolyzer; An electrolyte, wherein the electrolyte is disposed inside the electrolytic cell; The anode according to any one of claims 1 to 7; the anode rod is fixed to the wall of the electrolytic cell, and the anode active component is at least partially immersed in the electrolyte; A cathode is at least partially immersed in the electrolyte and is arranged opposite to the anode.
10. A method for electroplating a PCB board using the electrolytic device as claimed in claim 9.
Citation Information
Cited By
Anode with three-dimensional structure as well as preparation method and application of anode
CN120291185A